Bisphosphonate and risk of cancer recurrence: protocol for a systematic review, meta-analysis and trial sequential analysis of randomised controlled trials. Issue 4 (21st April 2015) - Liu, Yupeng; Du, Chen; Zhang, Yuxue; Zhao, Shu; Zhao, Lina; Li, Pengfei; Hu, Fulan; Zhu, Lin; Liu, Yanlong; Pang, Da; Zhao, Yashuang
Abstract : Introduction: No consensus exists on the associations between adjuvant treatment with bisphosphonates and cancer recurrence risk among patients with primary early-stage cancers. We plan to perform a comprehensive systematic review, study-level meta-analysis and trial sequential analysis of randomised controlled trials to comprehensively summarise evidence of the bisphosphonate treatment for difference cancers. Methods and analyses: We will report our results according to the PRISMA guideline. The primary outcomes include any cancer recurrence and bone metastasis and secondary outcomes include events of local recurrence, regional recurrence or non-skeletal distant metastasis, disease-free survival and overall survival. We will perform systematic electronic searches and other manual searches. To be conservative, all statistical analyses will be conducted with random-effects models. Cumulative meta-analyses and trial sequential analyses will be performed to assess whether and when firm evidence is reached. Various sensitivity analyses and rigid publication bias analyses will be performed to challenge the consistency and robustness of results. We will also grade the quality of evidence with the GRADE system. Ethics and dissemination: Ethical approval is not required in this study. The findings will be submitted for publication in a peer-reviewed journal and also presented at relevant national and international conferences. Trial registration number: PROSPERO CRD42014014699.